Pengaruh Self Esteem dan Kecerdasan Intelektual Terhadap Resiliensi Belajar Siswa Madrasah Aliyah Negeri 1 Deli Serdang - Suci Soleha; Asih Menanti; Hasanuddin Hasanuddin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This research uses quantitative methods. The purpose of this study was to determine the effect of self-esteem and intellectual intelligence on student learning resilience. The population is 120 students and a sample of 60 is taken using a random sampling technique. The results showed that there was a significant positive effect of self-esteem on student learning resilience, where the coefficient rx1y = 0.539 with p = 0.000, which means the better self-esteem, the better learning resilience. The coefficient of r squared self-esteem with the dependent variable learning resilience is r2 = 0.439. This shows that learning resilience is formed by self-esteem with a contribution of 32.30%. The intellectual intelligence variable has a significant positive effect on learning resilience where the coefficient rx2y = 0.290 with p = 0.000, this means that the better intellectual intelligence, the better learning resilience. The r-squared coefficient of intellectual intelligence on the dependent variable of learning resilience is r2 = 0.401. This shows that learning resilience is formed by intellectual intelligence of 11.60%. The variables of self-esteem and intellectual intelligence have a significant positive effect in simulation on learning resilience where the coefficient r = 0.439; with p = 0.000 means p < 0.010. The determinant coefficient (r2) of the influence of self-esteem and intellectual intelligence on learning resilience is r2 = 0.439. This shows that resilience is formed by self esteem and intellectual intelligence together with a contribution of 43.90%.